Factors Driving Soil Respiration Rate After Different Fertilizer Sources Addition - Yukun Zou; Ying Shan; Zhengfu Yue; Paola Gioacchini; Daniela Montecchio; Francesca Gaggia; Daniele Alberoni; Loredana Baffoni; Qiaoyan Zhang; Peng Xiong; Claudio Marzadori; Diana Di Gioia (Agronomy)
Soil respiration is a critical process that regulates key ecosystem functions such as climate control, nutrient cycling, and plant productivity. Soil texture, nutrient availability, and microbial communities can all influence soil respiration, yet our understanding of their relative importance remains limited. This study aimed to investigate how different factors—like soil texture, nutrient additions, and microbial communities—contribute to soil respiration and define their specific roles in its variability. Using a microcosm experiment with various fertilizers and two soil types (Navarra, a silty clay soil, and Saponi, a sandy soil), we measured changes in both biotic and abiotic factors. A multiple linear regression analysis revealed that, among other biotic and abiotic factors, soil clay content, soluble nitrogen levels, bacterial abundance, and α-diversity significantly impacted soil respiration, together accounting for over 60% of its total variance. Structural equation modeling indicated that microbial communities made the greatest contribution to respiration at 30.84%, followed by soil texture at 19.63%. Overall, biotic factors were found to play a more significant role in driving soil respiration rates compared to abiotic factors, with edaphic properties having a greater influence than fertilizer additions.